2005
DOI: 10.1523/jneurosci.4175-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

β-Adrenergic Receptor Activation Facilitates Induction of a Protein Synthesis-Dependent Late Phase of Long-Term Potentiation

Abstract: Long-term potentiation (LTP) is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
239
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(253 citation statements)
references
References 90 publications
(143 reference statements)
11
239
2
1
Order By: Relevance
“…Alternatively, or in addition, the BLA stimulation could lower the threshold for translation such that it would occur in synapses that were only weakly active during training. In support of this observation, recent findings indicate that pairing of subthreshold electrical stimulation with ␤-adenoreceptor activation is sufficient to induce long-lasting LTP in a hippocampal slice preparation and that this effect requires local, dendritic protein synthesis but is independent of transcription (34). The net effect of either of these two possibilities would be a strengthened network of synaptically coupled cells encoding relevant information about the IA training.…”
Section: Discussionmentioning
confidence: 78%
“…Alternatively, or in addition, the BLA stimulation could lower the threshold for translation such that it would occur in synapses that were only weakly active during training. In support of this observation, recent findings indicate that pairing of subthreshold electrical stimulation with ␤-adenoreceptor activation is sufficient to induce long-lasting LTP in a hippocampal slice preparation and that this effect requires local, dendritic protein synthesis but is independent of transcription (34). The net effect of either of these two possibilities would be a strengthened network of synaptically coupled cells encoding relevant information about the IA training.…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, treatment with the b-receptor antagonist propranolol alone did not affect extinction memory, suggesting that breceptor activation is not involved in the consolidation of extinction (Cain et al, 2004;Rodriguez-Romaguera et al, 2009). Electrophysiological studies have demonstrated that b-receptor activation induced by NE could not induce hippocampal long-term potentiation but lowered the subthreshold stimulus response to long-term potentiation (Gelinas and Nguyen, 2005;Katsuki et al, 1997;Thomas et al, 1996;Tully et al, 2007). The enhancing effect of NE on extinction may be attributable to an influence on emotional arousal and attention (Mason, 1983) or the promotion of the intrinsic excitability of neurons responsible for extinction memory (Mueller and Cahill, 2010).…”
Section: Mechanism That Underlies the Role Of Hippocampal Ne In The Pmentioning
confidence: 99%
“…Interestingly, propranolol does not seem to block the initial consolidation of conditioned fear memories. Although the exact mechanism by which propranolol impacts reconsolidation is unknown, the effects of beta-adrenergic receptor blockade on reconsolidation may be due to the fact that these receptors modulate protein synthesis and thereby regulate long-term memory storage (Gelinas and Nguyen, 2005).…”
Section: Reconsolidationmentioning
confidence: 99%